Anti-NMDA Encephalitis: An Uncommon, Autoimmune Mediated Form of Encephalitis - Azizyan, Avetis (J Radiol Case Rep, 2014)
We report an interesting case of a 19 year old female with findings on MRI suggestive of viral encephalitis. An extensive workup was negative for infectious causes and she was subsequently diagnosed with anti-NMDA encephalitis. Anti-NMDA encephalitis is a highly lethal but treatable form of autoimmune encephalitis that has recently been characterized. It is frequently found in young women and associated with an underlying teratoma. Although rare, this diagnosis should be considered in young females for whom a rapid onset of encephalitis cannot be explained by more common causes.